Efficiency assessment of the PSI-20 enterprises using Stochastic Frontier Analysis - Ferreira, N. B.; Menezes, R. (Sixth Annual American Business Research Conference, 2014)
The aim of the study is to assess the technical efficiency (TE) of the individual companies and their respective groups of the Portuguese stock market by using “interest income”, “depreciation”, and “cost of goods”, “employees and net sales” as exogenous input variables in a Stochastic Frontier Analysis (SFA) model. The TE of the PSI-20 enterprises index is estimated exploring what factors contribute to efficiency variability, applying the SFA approach main advantage which lies in its potential to discriminate between measurement error and systematic inefficiencies in the estimation process. The results reveal that TE is higher for the enterprises in industry, construction and distribution economic sectors whereas the commercial banking sector has the lowest TE scores. The “employees” and “depreciation” variables are the factors that most contribute to the stock market inefficiency.